Problem drinking and the interaction of reward, negative emotion, and cognitive control circuits during cue-elicited craving - Thang M. Le; Yu Chen; Shefali Chaudhary; Chiang-Shan R. Li (Addiction Neuroscience, 2022)
Individuals engage in alcohol consumption to seek reward and/or alleviate negative emotions. The neural processes subserving reward response and negative emotion thus likely play important roles in motivating alcohol use. Cognitive control, in contrast, is thought to regulate these motivational processes to keep drinking in check. As such, the balance between motivational and control processes may determine drinking behavior. Importantly, this balance is likely dictated by individual differences in drinking motives, including positive alcohol expectancy and perceived social isolation. Here, we characterized how the relative strength of the reward, negative emotion, and control circuit activities during alcohol cue exposure predicted alcohol use severity in 71 adult drinkers. Path models were employed to delineate the relationships between the neural, psychological, and drinking measures. We found that positive alcohol expectancy was associated heightened craving and greater activity of the reward relative to cognitive control circuit during cue exposure. The higher this circuit activity difference, the more severe subjects’ drinking. A similar relationship was found for social isolation, craving, activity difference of negative emotion vs. cognitive control circuits, and alcohol use severity. Thus, distinct neural pathways motivate alcohol use through reward seeking and negative emotion. By characterizing the neural circuits underlying cognitive control and motivational processes, the current study sheds light on how positive and negative reinforcement perpetuates problem drinking.